A Survey on Unimodal, Multimodal Biometrics and Its Fusion Techniques - S. Raju, A.; Udayashankara, V. (International Journal of Engineering and Technology, 2018)
Presently, a variety of biometric modalities are applied to perform human identification or user verification. Unimodal biometric systems (UBS) is a technique which guarantees authentication information by processing distinctive characteristic sequences and these are fetched out from individuals. However, the performance of unimodal biometric systems restricted in terms of susceptibility to spoof attacks, non-universality, large intra-user variations, and noise in sensed data. The Multimodal biometric systems defeat various limitations of unimodal biometric systems as the sources of different biometrics typically compensate for the inherent limitations of one another. The objective of this article is to analyze various methods of information fusion for biometrics, and summarize, to conclude with direction on future research proficiency in a multimodal biometric system using ECG, Fingerprint and Face features. This paper is furnished as a ready reckonerÂ  for those researchers, who wish to persue their work in the area of biometrics.Â Â
Keywords: Authentication; verification; unimodal; multi-modal; face; finger; ECG; biometrics.